Sisters by choice - Mallery, Susan (Toronto, Ontario : Mira, 2021)
"After her cat toy empire goes up in flames, Sophie Lane returns to Blackberry Island, needing to be close to family. As she rebuilds her business, small-town life reveals a big problem: only if she can let go and let others in will she find the happiness and love that have eluded her. Her cousin Kristine has become defined by her relationship to others. She's a wife, a mom. Now she wants something for herself --a sweet little bakery just off the water. She knew changing the rules wouldn't be easy, but she never imagined she'd have to choose between her marriage and her dreams."--Back cover.
Includes a reader's guide and an excerpt from The vineyard at Painted Moon.
Keywords: Cousins -- Fiction; Man-woman relationships -- Fiction; Interpersonal relations -- Fiction; Islands -- Washington (State) -- Fiction; Domestic fiction; Romance fiction